Headstall - Phillips, Jolyn (Multilingual Margins: A journal of multilingualism from the periphery, 2024)
My father is the healthiest I have ever seen him. He is brown again. His liver is healing. His eyes are glistening because they are happy to see me not because he is too intoxicated to talk. His beard is shaven, white stubble sitting quietly on his skin. His hair is shaven with a no.2 blade. He is spick ’n span. The last time he was sober he was attending my book launch with my mother (legally blind), aunt, uncle (who is blind now). My father was agitated in the bookshop and found every utterance and the fidgeting of my mother a disturbance to his church. My mother was the same. They argued like crumpled up paper. I hugged him sort of reluctantly since he always reeked of alcohol. It would sweat out of his pores. He was shaking and smoking, leaning against the bookshelf, completely out of place in his funeral best.